Implementation of Guided Inquiry Model with MURDER Strategy to Improve Elementary School Students' Science Process Skills - Arif Mishbah Suryawanto; Bambang Subali; Sri Haryani (Universitas Negeri Semarang, 2022)
Science learning is an educational activity that emphasizes the development of students' abilities and skills in learning. One crucial skill that students need to master in the learning process is science process skills. Science process skills enable students to independently discover concepts from various learning sources through exercises conducted during the learning process. This study aims to determine the effectiveness of the guided inquiry model with the MURDER strategy in improving students' scientific process skills. The method used in this study was quasi-experimental. The sample consisted of fifth-grade students from SDN 262 Panyileukan, Bandung City with 50 students in the experimental group and 50 students in the control group. The research results showed that the average post-test score obtained by the experimental group was 84.45, which was higher compared to the control group's score of 72.71. Additionally, the n-gain test results for the experimental group yielded a score of 0.58, while the control group had a score of 0.31. In conclusion, the guided inquiry model with the MURDER strategy was effective in improving students' science process skills.